PURPOSE AND TASKS OF BUSINESS PROCESSES IN INSURANCE ACTIVITY - Yakubova N.T. (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Business processes directly affect the sale of insurance products and the provision of services in accordance with the terms of the contract. In the organization of business processes in insurance activities, it is necessary to take into account such factors as enriching the database of insurance products, studying the demand and supply in the market.